Learning science towards a sustainable development - Costa, Manuel F. M. (2008)
The learning of sciences can be very stimulating. One cannot say there exists a perfect pedagogical method but our experience proved that actually going through the situations makes it possible for the students to learn the concepts more effectively and efficiently. Concrete experiences help students acquire knowledge with more ease [1]. The objective of the project herein reported is to get the students to learn science and simultaneously awaken to the principles of sustainable development. In the context of the programs of various disciplines, the use of a general and globalizing theme will allow to integrate various areas of knowledge and contribute to better learning. As collateral objectives, this project also intends to promote the level of literacy of the students and consequently of the society they belong to [2]. The United Nations entitled 2003-2012, the Literacy decade. Scientific literacy is fundamental for the development of our societies and humanity. The project will be implemented in other schools, located in mountain regions, in different European countries, that will share our experiences and knowledge. A number of exchange visits of groups of teachers and students will be organized in order to enhance the sense of European citizenship among the participants in the project and there schools. Science fairs will be organized where the work developed will be presented to the community.